ASSESSMENT OF GENETIC AND REPRODUCTIVE TOXICITY OF TONGKAT ALI PLUS® - EL MAKAWY I. AIDA,; BARAKAT ALAA,; OMAR M. HAFEZ,; SALAH M. HASSAN,; MENNAT ALLAH M. MAHMOUD,; SAID A. TAYEL, (International Journal of Pharma and Bio Sciences, 2016)
Tongkat Ali Plus® is a mixture of Eurycoma longifolia Jack and Lepidium meyenii powder as active ingredients. The objective of the present study is to evaluate the potential genotoxicity (in vivo &in vitro) and developmental toxicity of Tongkat Ali plus®. Bacterial reverse mutations assay was performed in Salmonella typhimurium strains and Escherichia coli (WP2-uvrA). In addition, chromosome aberrations and micronucleus assays were studied to investigate the in vivo genotoxicity in bone marrow cells of rats. Tongkat Ali plus® treated female and male rats were mated to evaluate the reproductive toxicity of Tongkat Ali plus® on female and developmental toxicity on their offspring. Results revealed that Tongkat Ali Plus® did not cause neither in vitro genotoxicity (at dose levels tested were 1750, 875, 175, 87.5,43.7 and 17.5 µg/plate) nor in vivo genotoxicity (at dose levels 250, 500 and 1000 mg/kg for consecutive 14 days). In addition, Tongkat Ali Plus® did not show obvious alteration in the reproductive performance or fetal development (at dose levels 1000, 375, 125 mg/kg for 14 days). Based on these endings, we can conclude that the use of Tongkat Ali Plus® in traditional medicine poses no risk.